Targetoid hemosiderotic melanocytic nevus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2016)
When we type in Pubmed “targetoid “ appear 230 reports which are divided mainly into two categories: those with multiple lesions, ranging from hemorrhagic edema of the newborn to bites of bedbugs, and those with only one hemorrhagic targetoid lesion around a neoformation. In the latter case we are dealing almost exclusively with a lesion that is called targetoid hemosiderotic hemangioma. It is really a hemolymphatic malformation (1) that spontaneously or following trauma undergoes a hemorrhage; the latter then spreads to the surrounding skin. However, this bleeding with centrifugal evolution is not exclusive of targetoid hemangioma. It can be found in other benign lesions, especially in melanocytic nevus. The morphological variation of targetoid hemosiderotic melanocytic nevus is so sudden as to exclude a malignant transformation (2).